STRENGTHENING UNDERSTANDING OF ANEMIA PREVENTION IN ADOLESCENT FEMALES THROUGH HEALTH EDUCATION: PENGUATAN PEMAHAMAN PENCEGAHAN ANEMIA PADA REMAJA PUTRI MELALUI PENDIDIKAN KESEHATAN - Isni, Khoiriyah; Santri, Ichtiarini Nurullita; Maulana, Muchsin (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Anemia is a hematological disorder characterized by a reduced erythrocyte count or hemoglobin concentration, resulting in a decreased oxygen-carrying capacity of the blood. Adolescent females, especially those living in suburban areas, are at a high risk of developing anemia. The Kalibawang Subdistrict in Kulon Progo Regency has been reported to have the highest distribution rate of iron (Fe) tablets. However, many adolescent females in the area still demonstrate limited knowledge about anemia. Moreover, they have never consumed or received iron tablets from local community health centers. Objective: This activity aimed to enhance knowledge about anemia and promote adherence to iron supplementation among adolescent females. Method: The methods employed in this community service program included health education sessions and blood pressure screenings conducted among female students at SMK 1 Kalibawang. The activity was evaluated using questionnaires administered before and after the intervention. Results: The findings revealed an increase in the average knowledge scores related to anemia among the participants after the health education intervention, indicating its effectiveness in improving understanding of the topic. Notably, none of the eleven participants showed a decrease in their scores from the pre-test to the post-test. Conclusion: Overall, the adolescent females demonstrated adequate knowledge regarding anemia following the intervention. It is recommended that the school establish collaboration with the Kalibawang Community Health Center to facilitate the free provision of iron tablets and ensure regular monitoring of their consumption.